MONGOLIAN STATE LEGAL SANCTIONS AND NATIONAL MEMORY - Ichinnorov Oyun; Jalbajav Nanzad (International Journal of Innovative Technologies in Social Science, 2026)
This article explores the connection between Mongolia’s legal and historical memory and national memory. National memory encompasses the principles, goals, orientations, and heritage of the nation's struggle for survival, deeply rooted in history, culture, ideology, religion, morality, and legal consciousness.The research employed a comparative analysis of historical documents and scholarly works. A key aspect of Mongolia's legal tradition is the “Great Government” law established by Genghis Khan in 1206, a valuable legacy of statecraft and legal science for Mongolians and humanity worldwide.The article highlights fundamental principles of Mongolian legal thought, including justice, the rule of law, legal integrity, environmental protection, and legal education. These principles form the basis of national memory and legal consciousness, spanning from the Great Mongol Empire to the Yuan Empire, the Bogd Khanate of Mongolia, and the Mongolian People’s Republic. The study underscores the significance of studying and preserving these traditions to uphold historical truth and instill patriotic ideals in the younger generation.